Application of Chinese Paper-Cutting Art to Create 3D Illustrations in Children’s Literature - Su, Jie; Chaetnalao, Atithep (Journal of Fine and Applied Arts Khon Kaen University, 2024)
Children’s picture books are one of the first choices for early childhood education, which greatly affects children’s appreciation ability and way of thinking (Yilmaz, R. M., Kucuk, S., & Goktas, Y. 2017). However, most of our country’s children’s picture books are purchased from overseas, and the application and innovation of traditional paper-cutting in the field of modern design is not enough (Child, J., & Rodrigues, S. B. 2005). The purpose of this study is: 1) To research and analyze the role of inherited art in the production of children’s picture books. 2) To suggest a new technique for Chinese paper cutting art in the creation of 3D Illustrations. 3) To create content and illustrations aligning with children’s cognitive and physical development. Through case analysis, literature review, case study, and methods of asking experts, the design practice of children’s picture books with the characteristics of paper-cutting art is carried out. The results of the research are: Paper-cutting art allows creators to get rid of the constraints of the objective world and express their own artistic vision; it has developed new techniques for Chinese paper-cutting art in 3D illustration creation; the widely circulated local "Legend of Meishan Niang, the Hunting God of Western Hunan" is selected as the Paper-cut style picture book 3D illustration creation content to create 3D illustrations suitable for children. The research conclusions are: 1. Paper-cut art allows creators to get rid of the constraints of the objective world and express their own artistic vision. The combination of paper-cut patterns breaks the barriers of realist aesthetics, and the images created in unique forms embody the aesthetic expression of surrealism. 2. The new technology of Chinese paper-cut art in 3D illustration creation can help children better accept and understand pictures and improve interactivity. 3. Select the widely circulated local legend "The Legend of Meishan, the Hunting God in Western Hunan" to create a 3D illustration suitable for children. These illustrations promote the innovative application of paper-cutting art in the creation of children’s illustrations, and promote the exploration of paper-cutting art in the creation of children’s literature. It is hoped that this research can contribute to the inheritance and development of paper-cutting art.